Price volatility across scales and farmer maneuvering in Lao cassava markets - Nguyen, Anh-Thu; Huellen, Sophie van; Newby, Jonathan Craig (Informa UK Limited, 2023)
Lao PDR is undergoing a rapid agrarian transformation, underpinned by a growing commercial production of commodity crops such as cassava by smallholder farmers. The global nature of commodity crop markets increases the exposure of potentially vulnerable smallholder farmers to global price dynamics. We apply a cross-scalar and mixed-methods approach to investigate the role of institutional structures and the global-regional-domestic context in local price formation mechanisms at the farm gate. We focus our analysis on policy shocks created by the Chinese government’s temporary purchase and storage policy (TSPS) for maize, and the experience and price risk mitigation strategies of smallholder cassava farmers in Lao PDR during this period. We find that the price level and volatility experienced by farmers are shaped by local-level market structures as much as global price dynamics and regional trade integration, demonstrating the importance of institutions across scales in price formation and transmission.